2008
DOI: 10.1523/jneurosci.5112-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic Deafferentation of Prefrontal Cortex Increases Sensitivity to Cross-Modal Distractors during a Sustained Attention Task

Abstract: The effects of restricted cholinergic deafferentation of prefrontal cortex in rats on sustained attention were assessed. Attentional demands were increased by presentation of distractor stimuli in a different modality (auditory) or the same modality (visual) as target stimuli. Additionally, the effects of the regularity of the distractor on rats' ability to disregard this stimulus were assessed by testing different frequencies of stimuli for each modality. Cholinergically lesioned rats were more sensitive to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 50 publications
(68 reference statements)
2
66
1
Order By: Relevance
“…To achieve a more graded level of performance on signal trials, the middle signal duration could be increased. In fact, Newman and McGaughy (2008) used a 100 ms, rather than 50 ms, middle signal duration and they found a greater distinction in performance between 100 ms and 25 ms than we did between 50 ms and ms. Future studies could confirm this using the touchscreen boxes.…”
Section: Discussioncontrasting
confidence: 56%
“…To achieve a more graded level of performance on signal trials, the middle signal duration could be increased. In fact, Newman and McGaughy (2008) used a 100 ms, rather than 50 ms, middle signal duration and they found a greater distinction in performance between 100 ms and 25 ms than we did between 50 ms and ms. Future studies could confirm this using the touchscreen boxes.…”
Section: Discussioncontrasting
confidence: 56%
“…The results also suggest the role of the ACC is dissociable from the prelimbic cortex in rats. Previous work in our lab has shown that neurochemical and regionally specific damage to the prelimbic cortex does produce a general increase in distractibility that is not limited to previously reinforced stimuli as found after ACC damage (Newman & McGaughy, 2008). Several studies suggest the prelimbic cortex (dorsolateral prefrontal cortex in primates) has also been shown to play a substantial role in conflict monitoring (Banich et al, 2000; Chen et al, 2006; Erickson et al, 2004; Milham, Banich, Claus, & Cohen, 2003).…”
Section: Discussionmentioning
confidence: 70%
“…Impairments in attentional set shifting result from damage to the PrL in the rat [15,28,29] or to the dorsolateral PFC in humans [11] and nonhuman primates [13,14]. Specifically, damage to the noradrenergic afferents to the PrL impairs ED performance but does not affect performance on any other stage of the attentional set-shifting task [28,38].…”
Section: Discussionmentioning
confidence: 99%
“…Methods are similar to those described in previous work [20,28,29]. First, the rats were trained to dig for reinforcement in weighted terracotta pots (height of 10 cm, internal diameter of 10.2 cm) that were affixed to the floor of the testing box with velcro (Manchester, N.H., USA).…”
Section: Methodsmentioning
confidence: 99%